Critical thinking strategies in EFL teaching and learning - Букенбаев, А.Н.; Шагатаева, З.Ж. (My University, 2016)
The aim of this article is to share both theoretical and practical ideas about critical thinking development within English language teaching/learning contexts. The authors seek to answer two questions, namely, why to integrate and develop critical thinking in ELT, and how to create lessons including an element of critical thinking development. A lesson plan is provided demonstrating the elements of critical thinking strategies in ELT.
Keywords: Critical thinking; English language teaching/learning; lesson plan; ABCD model; cognitive and affective domains; critical thinking strategies